Educational Responsibility in The Perspective of Islamic Educational Counseling - Nasution, Zulkipli; Lubis, Saiful Akhyar (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Islamic teachings emphasize that every human being can protect his family from the dangers of the torment of hell fire, namely by educating children as well as possible according to the Word of Allah SWT. in surah At-Tahrim verse 6. In essence, the responsibility of education is a big and important responsibility. Because, in its operational setting, education is the provision of guidance, assistance and assistance from adults or people responsible for education to children who are not yet mature. Adult from a spiritual and physical perspective in piety to Allah SWT, which is shown in the form of responsibility for all attitudes and behavior towards oneself, society, and towards Allah SWT. The concept of educational responsibility in Islamic education in the perspective of Islamic counseling includes: 1) Responsibility for Faith Education (Tawhid), 2) Responsibility for Moral Education, 3) Responsibility for Physical Education, 4) Responsibility for Education of Reason/Ratio, 5) Responsibility for Heart/Psychic Education, 6) Responsibility for Social Education.